2008
DOI: 10.1080/00288230809510472
|View full text |Cite
|
Sign up to set email alerts
|

Pasture responses to phosphorus and nitrogen fertilisers on east coast hill country: 3. Production from steep slopes

Abstract: Aseries of trials was established in 2000, and measured until 2002, down the east coast of New Zealand on seven farms with contrasting amounts of spring-summer rainfall and resultant pasture growth. The aim was to evaluate the pattern of pasture responses to a range of nitrogen (N) fertiliser rates and associated soil phosphorus (P) levels generated by a range of P fertiliser treatments. Small plots excluded from grazing were established on steep (about 20 degrees slope) sites containing pastures that had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…The same conclusion was reached by Gillingham et al (1998) as a result of earlier trials on summ er dry hill country near Waipawa in Hawke's Bay.…”
Section: Sitesupporting
confidence: 67%
See 1 more Smart Citation
“…The same conclusion was reached by Gillingham et al (1998) as a result of earlier trials on summ er dry hill country near Waipawa in Hawke's Bay.…”
Section: Sitesupporting
confidence: 67%
“…Trial management may therefore impose a greater than desirable amount of shading on clovers present, but this would be similar to that encountered on many rotationally grazed hill farms. Gillingham et al (1998) reported a reduction in clover content of hill pastures that had received N fertiliser and were rotationally grazed by ewes and cattle.…”
Section: Sitementioning
confidence: 99%
“…The use of N fertiliser in hill country farming has increased considerably in recent years (MacLeod & Moller 2006). A range of N fertiliser responses of 1Á33 kg DM/ kg N have been reported in hill pastures (Luscombe 1980;Ball & Field 1982;Lambert et al 1986;Clark & Lambert 1989;Gillingham et al 1998;Blennerhassett 2002;Gillingham et al 2007Gillingham et al , 2008a. Factors affecting the magnitude of response include location (Ball & Field 1982;Gillingham et al 2008aGillingham et al , 2008b, fertiliser application rate Gillingham et al 2007Gillingham et al , 2008aGillingham et al , 2008b, season, slope (Ledgard et al 1983;Gillingham et al 1998;Blennerhassett 2002;Gillingham et al 2003), aspect (Blennerhassett 2002;Gillingham et al 2003) and pasture species composition (Ledgard et al 1982;Rumball 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Although considerable information exists about the relationship between the application of phosphorus fertiliser, pasture growth and the influence of topography (Lambert et al 1983(Lambert et al ,2000Gillingham et al 1998;Lopez et al 2003;Dodd et al 2004), up until now we have lacked the mechanism to apply variable rates of fertiliser to match the potential of the land. A variable rate control system designed by the New Zealand Centre for Precision Agriculture, Massey University in conjunction with Wanganui Aerowork Ltd has been developed, and commercial trials using this system have resulted in a ground resolution of 18 × 18 m. Figures such as 15-20 kg superphosphate SU -1 yr-1 wintered have been used as a broad recommendation (Morton & Roberts 1999); however the within-field variability of hillcountry pasture production is often overlooked.…”
Section: Introductionmentioning
confidence: 99%